Analisis Pengaruh Globalisasi terhadap Pola Belajar Siswa Sekolah Dasar dalam Mewujudkan SDGs Pendidikan Berkualitas - H. Priyono Tri Febrianto; Febrian Mahendra; Siti Khoiria; Widya Yasfi Nabila; Jesika Yulianti; Serafim Kristianingsih (Elementary Education Journal, 2026)
Background: This study aims to analyze the influence of globalization on the learning patterns of elementary school students in achieving quality education aligned with the Sustainable Development Goals (SDGs). The study is motivated by shifts in learning behavior due to rapid technological advancements and increased access to digital information. Method: This research uses a qualitative approach with a literature review design, utilizing secondary data from journals, books, and research reports published between 2022 and 2026. Data were collected through systematic literature review and analyzed using descriptive-analytical techniques. Result: Hasil penelitian menunjukkan bahwa globalisasi memiliki dampak positif dan negatif. Globalisasi meningkatkan akses informasi, literasi digital, serta keterampilan abad ke-21, namun juga menurunkan interaksi sosial, meningkatkan individualisme, dan melemahkan nilai budaya lokal. Oleh karena itu, diperlukan keseimbangan antara pemanfaatan teknologi dan penguatan karakter untuk mewujudkan pendidikan yang inklusif dan berkelanjutan. Implication: A balance is needed in the use of technology while still strengthening character values and local culture. In this regard, the roles of teachers, schools, and parents are very important in guiding the learning process so that it can adapt to global developments without neglecting social and cultural aspects, thereby achieving the goals of inclusive, high-quality, and sustainable education effectively. Novelty: This research is important to conduct in order to examine in depth how globalization influences changes in learning patterns as well as the dynamics of social interaction among elementary school students.